A CONTROVERSIAL ON THE DIAGNOSIS OF CHRONIC BULLOUS TYPE MUCOCUTANEOUS DISEASE INVOLVING ORAL MUCOSA (A CASE REPORT) - Isadora Gracia; Harum Sasanti (Faculty of Dentistry, Universitas Indonesia, 2006)
A case of chronic bullous type mucocutaneous disease involving oral mucosa was reported from a 56 years old man with never healing oral ulcers and wound on the perianal skin for three years. There were also red and black spots on the limb and back skin and a lesion on nail. Painful oral lesion consisted of mucous erosion, desquamative gingivitis, and sloughing area on palate and tongue. The patient is diabetic. The first perianal skin diagnosis was granulomatous candidasis with differential diagnosis pemphigus vegetates and acuminarum condiloma. However the histopathologic examination did not support these diagnosis. After several histopathologic examinations, the latest perianal skin diagnosis was lichen planus with differential diagnosis granulomatous vasculitis, bowenoid papulosis and pyodema gangrenosum. Other skin diagnosis was erythema multiforme. Oral diagnosis was mucous membrane pemphigoid with differential diagnosis lichen planus, Behçet's syndrome and erythema multiforme. Oral histopathologic examinations showed a sub-epithelial blister, which supported mucous membrane pemphigoid. A lip balm, prednisone 5 mg oral rinse and multivitamins were given but oral improvement started after blood sugar level was controlled. Conclusion: It is not yet known whether skin and oral mucous lesions are from the same disease or not.